BOOK ABOUT M.M. DALGAT. Review of the book by Dalgat E.M., Magomedov S.A. «Magomed Dalgat: epoch, life, activity». - Makhachkala: GAU RD «Dagestanskoe knizhnoe izdatel’stvo», 2015 - Aliev, B G; Inozemceva, E I (History, Archeology and Ethnography of the Caucasus, 2016)
-